Bioethanol Levels of Dragon Fruit (Hylocereus polyrhizus) Peel with the Addition of Blend Crude Cellulase Enzyme from Trichoderma reesei and Aspergillus niger - Trianik Widyaningrum; Masreza Parahadi (Universitas Gadjah Mada, 2020)
The petroleum fuel crisis shows that Indonesia's fossil energy reserves are limited. It is necessary to develop an environmentally, friendly and sustainable alternative energy, one of which is bioethanol. This study aims to determine the bioethanol levels of dragon fruit (Hylocereus polyrhizus) peel with the treatment of cellulase enzymes from Trichoderma reesei and Aspergillus niger. This research was an experimental study that uses steps such as making dragon fruit peel substrate and filtrate, cellulose degradation with enzymes from Trichoderma reesei and Aspergillus niger and inoculating with yeast (Saccharomyces cerevisiae) with a fermentation time of 96 hours and then measured reducing sugar levels with the method of DNS, distillation, and the measurement of bioethanol levels using alcohol meters. The results have shown that using enzymes from Trichoderma reesei and Aspergillus niger can increase the reduction of 49.68 % sugar levels in the treatment of T.reesei: A.niger (3: 1) and produce the highest bioethanol level, which is 2.46 % in the treatment of T.reesei: A.niger (2: 1)